2020
DOI: 10.3389/fonc.2020.01330
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Landscape and Prognostic Immune Key Genes Potentially Involved in Modulating Synaptic Functions in Prostate Cancer

Abstract: Background: Increasing evidence has indicated an association between differentially expressed genes (DEGs) in tumor-infiltrating immune cells (TIICs) and clinical outcome. The aim of this research is to investigate the influence of tumor microenvironment on the gene expression profile of TIICs and to identify their potential markers for modulating immune cell function in prostate cancer. Methods: In our research, CIBERSORT algorithm was utilized to calculate the proportion of the TIICs in 164 tumor and 18 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…GO analysis was used to evaluate the potential functions and degree of enrichment of the DEGs in biological processes (BP), cellular components (CC), and molecular functions (MF). Kyoto Gene and Genome Encyclopedia (KEGG) database with a P-value of <0.05 was used to systematically analyze the differences in gene function [ 11 ]. In addition, gene set enrichment analysis (GSEA) was used to determine the statistically significant and concordant differences between the two biological states of primary and bone metastatic CRPC tumors.…”
Section: Methodsmentioning
confidence: 99%
“…GO analysis was used to evaluate the potential functions and degree of enrichment of the DEGs in biological processes (BP), cellular components (CC), and molecular functions (MF). Kyoto Gene and Genome Encyclopedia (KEGG) database with a P-value of <0.05 was used to systematically analyze the differences in gene function [ 11 ]. In addition, gene set enrichment analysis (GSEA) was used to determine the statistically significant and concordant differences between the two biological states of primary and bone metastatic CRPC tumors.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing evidence suggests that polarized NK cells are present in the peripheral blood of patients with several types of cancer (9,10,15,16,29,30,33) and their altered profile could be a relevant feature. The idea that NK cells can be envisaged as biomarkers for PCa have been previously explored (26,(34)(35)(36). Also, a clinical trial is exploring the significance of circulating NK cells in metastatic PCa (https://clinicaltrials.gov/ct2/show/ NCT02963155).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cheng C et al claimed RAC3 promoted proliferation, migration, and invasion through PYCR1/JAK/STAT signaling in bladder cancer [ 39 ]. VCL has been reported as an important prognostic biomarker in prostate cancer [ 40 ]. Satow R et al reported that PDGFD promotes aggressiveness in prostate and colorectal cancer [ 41 ].…”
Section: Discussionmentioning
confidence: 99%